RETRACTED: Immunosuppressant MPA Modulates Tight Junction through Epigenetic Activation of MLCK/MLC-2 Pathway via p38MAPK - Khan, Niamat; Pantakani, D. V. Krishna; Binder, Lutz; Qasim, Muhammad; Asif, Abdul R. (Frontiers in Physiology, 2015)
Abstract Background Mycophenolic acid (MPA) is an important immunosuppressive drug (ISD) prescribed to prevent graft rejection in the organ transplanted patients, however, its use is also associated with adverse side effects like sporadic gastrointestinal (GI) disturbances. Recently, we reported the MPA induced tight junctions (TJs) deregulation which involves MLCK/MLC-2 pathway. Here, we investigated the global histone acetylation as well as gene-specific chromatin signature of several genes associated with TJs regulation in Caco-2 cells after MPA treatment. Results The epigenetic analysis shows that MPA treatment increases the global histone acetylation levels as well as the enrichment for transcriptional active histone modification mark (H3K4me3) at promoter regions of p38MAPK, ATF-2, MLCK and MLC-2. In contrast, the promoter region of occludin was enriched for transcriptional repressive histone modification mark (H3K27me3) after MPA treatment. In line with the chromatin status, MPA treatment increased the expression of p38MAPK, ATF-2, MLCK, and MLC-2 both at transcriptional and translational level, while occludin expression was negatively influenced. Interestingly, the MPA induced gene expression changes and functional properties of Caco-2 cells could be blocked by the inhibition of p38MAPK using a chemical inhibitor (SB203580). Conclusions Collectively, our results highlight that MPA disrupts the structure of TJs via p38MAPK-dependent activation of MLCK/MLC-2 pathway that results in decreased integrity of Caco-2 monolayer. These results led us to suggest that p38MAPK-mediated lose integrity of epithelial monolayer could be the possible cause of GI disturbance (barrier dysfunction) in the intestine, leading to leaky style diarrhea observed in the organ-transplanted patients treated with MPA.